Author Correction: Experimental observation of bulk nodal lines and electronic surface states in ZrB2. Issue 1 (December 2018) - Lou, Rui; Guo, Pengjie; Li, Man; Wang, Qi; Liu, Zhonghao; Sun, Shanshan; Li, Chenghe; Wu, Xuchuan; Wang, Zilu; Sun, Zhe; Shen, Dawei; Huang, Yaobo; et al.
The original version of this Article did not acknowledge Qi Wang as an equally contributing author. This has now been corrected in the HTML and PDF versions of the Article.